A comprehensive study on the effects of internal air jet piston on the performance of a JOME fueled DI diesel engine. (15th October 2019) - Jaichandar, S.; Thamaraikannan, M.; Yogaraj, D.; Samuelraj, D.
Abstract: In DI diesel engine, air-fuel mixing is a major parameter that affects the performance, emissions parameters and combustion characteristics. In-cylinder air motion and proper mixing of fuel have a strong effect on BTE, BSFC, UHC, CO, smoke and NOx emissions, because of improvement in the combustion of fuel. In this experimental investigation in order to enhance the performance of biodiesel-fueled diesel engine, the engine was tested using piston having internal air jets using 20% Jatropha Oil Methyl Ester-diesel blend (B20 JOME). For this purpose, the piston of the standard engine having Hemispherical Combustion Chamber (HCC) was reformed into Toroidal Re-entrant Combustion Chamber with internal air jets (TRCC-IAJ) that has the same volume as baseline HCC. The tests were performed at IMEP of 1.7, 3.2, 4.7, 6.2 and 7.7 bar with the standard injection timing and pressure. The test results show that the BTE and BSFC provide the best result for the modified piston compared to the original. The TRCC-IAJ reduced the smoke, CO and HC; while it showed the opposite effect with a sharp increase in NOx emissions. In overall, the results show that the modified piston TRCC-IAJ has improved the overall performance and emissions of the JOME-diesel blend. Highlights: Investigates the effects of Toroidal re-entrant with Internal Air Jets (TRCC-IAJ) in a DI diesel engine. Hemispherical (HCC) combustion chamber, Toroidal re-entrant combustion chamber (TRCC) and TRCC-IAJ were used. Test results showed that improved performance and emission characteristics for TRCC-IAJ. TRCC-IAJ has shown better combustion characteristics due to improved air-fuel mixing.